Teacher competence, school management, and organizational culture as joint drivers of teacher productivity: Evidence from SMA Negeri 66 Jakarta - Wahyudi, Didi (Privietlab, 2025)
This study investigates whether teacher competence, school management, and organizational culture jointly and separately shape teacher productivity in a public urban high school context. Using a census of 63 teachers at SMA Negeri 66 Jakarta, we administered multi-item Likert instruments aligned with national education standards and management/culture frameworks. Psychometric screening yielded high internal consistency across scales (α ≈ 0.88–0.96), and classical OLS assumptions (normality, homoskedasticity, linearity, absence of harmful multicollinearity) were satisfied. Bivariate analyses showed that competence had the strongest zero-order association with productivity (r ≈ 0.92; R² ≈ 81%), followed by organizational culture (r ≈ 0.61; R² ≈ 37%) and school management (r ≈ 0.44; R² ≈ 19%). In the simultaneous model, all predictors remained positive and significant, with combined explanatory power around 38–39% (p < .001). Notably, organizational culture exhibited the largest marginal coefficient when controlling for the other variables, indicating that a collaborative, disciplined, and trust-rich culture amplifies the translation of individual competencies into observable performance. Managerially, the results imply that targeted improvements in budgeting transparency and cycle discipline, structured peer learning (e.g., lesson study, peer observation), and timely, specific recognition can elevate productivity beyond its already favorable baseline. The findings support a triadic productivity model in which capability (competence), systems (management), and norms (culture) operate as complementary levers of performance.